The Governance Edge: Unlocking Renewable Energy Potential Through Board Leadership - Momin, Mujtaba; Naqvi, Ariz; Dsouza, Suzan (International Journal of Energy Economics and Policy, 2025)
The present study triangulates board gender diversity and board expertise with the use of renewable energy sources. The study reveals the association between these three variables, under the regimentation of control variables. The investigation, using a final dataset of 1892 firms from the European Union, deciphers their association to be influential in renewable energy use, to the extent of a statistically significant relationship. The decadal dataset between 2013 and 2023, sourced from the Refinitiv (Datastream) database, is processed using the STATA software package. The study magnifies the positive influence that board gender diversity has on renewable energy adoption, indicating that a higher proportion of female directors contributes to improved environmental performance and strategic commitment to sustainable energy practices. Simultaneously, board-specific skills are examined to assess their contingent effect on renewable energy investments. Findings suggest that while gender-diverse boards stimulate innovation and sustainability initiatives, an overemphasis on conventional expertise may foster a risk-averse approach, limiting renewable energy projects. This study is one of the few investigations contributing to the literature in this area, paving the way for future research to explore the interplay between corporate governance, board composition, and the transition toward a low-carbon economy, thus enhancing long-term sustainable global development.